Geometric Evaluation of Highways and Railroads on Safety at Crossings (Case Study of JPL 136 and JPL 138 Madiun City) - Nurhadi, Muhamad; Widi Astuti, Septiana; Dewi, Puspita (ASTONJADRO, 2024)
Railway and road transportation are land transportation that service users widely use because these modes play an important role in community activities, especially people on the island of Java. The train is a mass transportation with many advantages over other transportation, especially as a solution to the congestion problem in the country. Level crossing is a meeting between the railroad and the highway. Level crossings must meet the standard requirements set by the relevant agencies including geometric conditions, free space and wake space, and visibility so that level crossings are comfortable and safe for vehicles to pass through. The purpose of this study is to evaluate the geometric conditions, free space and shape as well as the visibility of level crossings. This study uses field observations and data from DAOP 7 Madiun to compare field conditions with requirements. The research was conducted at level crossings, namely JPL 136 and JPL 138 Kota Madiun.